2004
DOI: 10.1111/j.1085-9489.2004.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Shortcomings of Commodity‐based Technology in Input–Output Models: an Economic‐Circuit Approach

Abstract: The Make-Use Model serves as a basis for most national accounting systems as the System of National Accounts (SNA) and is acknowledged as the most suitable model for interregional analysis. Two hypotheses are traditionally made featuring either industry-based technologies (IBT) or commodity-based technologies (CBT). While industry-based technologies can be easily interpreted in terms of a demand-driven economic circuit, it will be shown that: (1) commodity-based technologies cannot be interpreted as a demand-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…ten Ra (1988) has understood that negative terms are not due to errors in the data but to the model. The present author (de Mesnard 2004) has shown that, if the model is interpreted in terms of circuit, it cannot be demand-driven as usual and the product-technology assumption corresponds to the so-called supply-driven Ghosh model, largely criticized (Dietzenbacher 1997;de Mesnard 2009). where x i is the output of industry i (x i > 0 for any i), w j the value added of industry j (w j > 0 for any j), q i the total production of product i (q i > 0 for any i) and e i is the amount of product i sold to final demand (e i > 0 for any i).…”
Section: Remind: Derivation Of Symmetric Io Tables With the Four Modelsmentioning
confidence: 88%
“…ten Ra (1988) has understood that negative terms are not due to errors in the data but to the model. The present author (de Mesnard 2004) has shown that, if the model is interpreted in terms of circuit, it cannot be demand-driven as usual and the product-technology assumption corresponds to the so-called supply-driven Ghosh model, largely criticized (Dietzenbacher 1997;de Mesnard 2009). where x i is the output of industry i (x i > 0 for any i), w j the value added of industry j (w j > 0 for any j), q i the total production of product i (q i > 0 for any i) and e i is the amount of product i sold to final demand (e i > 0 for any i).…”
Section: Remind: Derivation Of Symmetric Io Tables With the Four Modelsmentioning
confidence: 88%
“…For instance, de Mesnard [6] stated that the commodity technology hypothesis has to be rejected since it breaks the linkages of commodity flows internal to the industries. No information is available to determine which industry supplies a positive variation in final demand of a particular commodity.…”
Section: Background Contextmentioning
confidence: 99%
“…In many cases, the preferred solution has been to make the supply -use system square by aggregation, which leads to the loss of important information on detailed input breakdowns of certain industries. The appearance of negatives has also led other authors to talk about the implausibility of the two methods, especially the product technology assumption (see de Mesnard, 2004).…”
Section: Supply-use Based Input -Output Analysismentioning
confidence: 99%